Language evaluation by a speech therapist (I) - Arroyo Carreras, Alicia; Díaz Martín, María; López Sáiz, Laura; Ortega Navarro, María (Pulso. Revista de educación, 2004)
The significance and rationale behind conducting proper language assessments in children with developmental language disorders are underscored in this article. The article aims to provide guidance and support to language professionals who are involved in interventions for children with these disorders. It highlights the most relevant aspects that must be considered during the evaluation process and offers guidance on how to conduct this process. It approaches the evaluation process from a dynamic and flexible perspective, considering that every child is unique and therefore, each evaluation, although focusing on the same aspects, will be different. The most important aspect of the evaluation is the child. The article concludes by presenting a language evaluation protocol model that highlights all the important aspects that should be considered and present during the evaluation process. However, the presented protocol is open to any modifications or adaptations that the reader may find necessary while developing their own evaluation protocol.